Results Quantity Amount of Food Recording Expenditures on Food Waste Behavior in Households in North Bekasi, Bekasi City - Sawitri, Titis Retno; Sa’pang, Mertien; Noviati, Anugrah; Swamilaksita, Prita Dyani; Ronitawati, Putri (Asian Journal of Healthcare Analytics, 2025)
In addition to the food waste environment, this can also waste energy in meeting daily needs. The aim of this study is to understand the magnitude of waste from food waste behavior generated by households in urban areas. Based on the data results in daily waste disposal, it was found that vegetables constitute a significant portion of food waste. Meanwhile, in the waste generated from food storage, fruits were found to be the largest contributor. This disposal can occur due to the process of declining freshness in food, which leads to spoilage and ultimately ends up in the trash. The conclusion of this analysis found that there is a relationship between food purchasing and food storage with the occurrence of food waste.